2022
DOI: 10.37190/abb-01994-2021-01
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of total hip arthroplasty with a fully hydroxyapatite-coated stem: comparing thermoelastic stress analysis and CT-based finite element analysis

Abstract: Purpose: The aim of this study was to evaluate the stress distribution in a synthetic femur that was implanted with a fully hydroxyapatite-coated stem using thermoelastic stress and finite element analyses, and to clarify the differences in the stress distributions between these two methods. Methods: Thermoelastic stress analysis is a stress-analysis technique that employs the thermoelastic effect. Sinusoidal vertical loads were applied to the head of the stem placed on the synthetic femur, and surface stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The reduced rate of revision using collared stems has been reported in other studies without elaborating on the effect of sex or age. 18,19,27,28 Our findings emphasize the importance especially for female patients in all age cohorts, as the use of a collar was associated with a clear reduction in the rate of revision (Table II). Other studies have also shown good long-term results of certain uncemented designs of stem in the elderly, which is also reflected in the non-inferiority analysis of the Old cohort.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The reduced rate of revision using collared stems has been reported in other studies without elaborating on the effect of sex or age. 18,19,27,28 Our findings emphasize the importance especially for female patients in all age cohorts, as the use of a collar was associated with a clear reduction in the rate of revision (Table II). Other studies have also shown good long-term results of certain uncemented designs of stem in the elderly, which is also reflected in the non-inferiority analysis of the Old cohort.…”
Section: Discussionsupporting
confidence: 52%
“…Collared stems provide increased primary stability and a reduced risk of subsidence and early periprosthetic fracture. 18,19 The indications for their use have been extended from younger to elderly patients. 20 The aim of this study was to investigate the influence of stem design and the method of fixation on the revision rate, and immediate postoperative mortality rate, focusing on the patients' age and sex, based on the data available in the EPRD.…”
Section: Introductionmentioning
confidence: 99%
“…The stress distribution differs depending on the type of stem, and the contact condition of the stem influences stress distribution [ 13 , 29 ]. In addition, as this method can measure the stress at any point or area on the surface, it may be compared and validated using FEA and strain gauge methods [ 3 , 31 ].…”
Section: Discussionmentioning
confidence: 99%